Unveiling Gender Discrepancy in Open Access LIS Publications: A Case Study of Annals of Library and Information Studies - Daimari, Viv Ringsar; Verma, Manoj Kumar (Journal of Information and Knowledge, 2025)
The present study aims to investigate the authorship pattern, authors’ productivity, citation count and degree of collaboration in an open-access LIS journal Annals of Library and Information Studies through a gender lens. The raw data for the study are extracted from the Scopus database. The search has been initiated by selecting “Source title” and using the name of the journal “Annals of Library and Information Studies” as a keyword. A total of 393 documents were resulted in the initial search. Then the data was filtered by limiting the year range from 2014-2023 and considering only “Article” and “Review” as the document type. The final 294 documents which resulted after filtering relevant criteria are exported in .csv format and considered for the study. MS Excel is used for the analysis and authors’ genders are identified through the online software named Namsor. The research publications in the journal are contributed through various authorship patterns. Male authors are dominant over female authors in research productivity, number of research publications and citation count irrespective of collaboration or without collaboration. The degree of collaboration among authors considering male-to-male collaboration and female-to-female collaboration is lesser than the average degree of collaboration. However, female authors are contributing more research papers when they are in collaboration with male authors. The present study is the first systematic analysis regarding the publications of Annals of Library and Information Studies through gender lens. The results of the study will serve as a valuable reference for future researchers, think tanks of the LIS field and policymakers.